Pemanfaatan Birth Ball dalam Kala Satu Persalinan untuk Mempercepat Penurunan Kepala Janin - Nazla Anugerah Widia Hendri; Jumiati, Jumiati (Jurnal Anestesi, 2024)
The aim of this research plan is to determine the effectiveness of using a gym ball on lowering the head in pregnant women and speeding up the duration of labor. The method in this research is a case study using qualitative descriptive methods. The place of implementation is at PMB Rosita S.Tr Keb which is located at Citra Kencana Housing, Jl. Taman Karya No.17, Tuah Karya, Kec. Handsome, Pekanbaru City Riau 28293, Indonesia. The research was conducted on Mrs.  The types of data used are primary data and secondary data. Other research results indicate that the Pelvick Rocking Exercise can speed up the first stage of the active phase of labor in multigravida mothers. This is similar to the results of research which also shows that the gym ball technique with pelvic rocking can speed up the length of labor in the first stage of the active phase by 52.61% and in terms of descent and rotation of the fetal head at the beginning of the active phase (dilatation: 3-5 cm) and the second stage.